Objectives and Urgency of Fiqh Learning - Sabrina, Rifdah; Arifin, Zainul; Albizar, Albizar; Desvita, Annisa (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
Fiqh learning has a significant purpose in shaping students’ understanding and practice of Islamic teachings. This study aims to explore the objectives of fiqh learning, the position of fiqh within the curriculum of madrasahs and schools, as well as the role of fiqh in the development of students’ character. The method employed in this study is a literature review of various sources, including textbooks, scholarly articles, and curriculum documents. The findings indicate that the objectives of fiqh learning include strengthening faith, understanding Islamic law (syariah), and applying Islamic values in daily life. Fiqh holds an important position in the curriculum of madrasahs and schools as one of the subjects that support character and spiritual education. Furthermore, fiqh plays a role in shaping students’ character through the teaching of ethics, morality, and social responsibility. This study is expected to provide insights for educators and policymakers in developing a more effective curriculum.